Intelligent light control system (ILIC) - Badihah, Ismail (2016)
Intelligent Light Control(ILIC) is a system that will control the light by detecting the movement in a room. The system was developed because the lamp does not have ability to detect presence of human. People need to turn off the light manually. Besides, people rarely exposed to the statistic of energy consumption. Three objectives have been achieved from this system which is to develop a system that detect movement using camera and PIR sensor, to develop a light that automatically turn off when there are no movement and to record the energy consumption and display it in the report. In this system, the light in a room will automatically turn on when there is movement and the light will automatically turn off when there is no movement. The system will always detect the movement in a room. The system also provides web application to display energy consumption information and the total price. Furthermore, the system also allows the user to update the wattage of light, rates price per kwh and set the duration of time for light turn off through web application. All the data will be saved into the database and user will able view and print the statistic of energy consumption through web application.